Social Science Research in Southeast Asia: the Challenges of Studying Parliamentary Institutions - Ratih Adiputri (Center for Southeast Asian Social Studies (CESASS), 2019)
This paper introduces the challenges of studying parliamentary institutions in Southeast Asia. My focus of research is in three countries’ institutions: national parliaments of Indonesia, Malaysia and Singapore. While in Southeast Asia, it is widely known that studying issues of politics and institutions face challenges – compared to studying culture, for example, this view is arguably no longer valid, however with certainqualification.The comparison of parliamentary tradition between three countries – based on observation of the plenary session - reveals that the effectiveness of parliamentary works is related to parliamentary procedure, and even to the culture of work in the countries. Parliamentary structure, procedure and their political culture matters. Therefore, acknowledging these factors will give rise to more research opportunities, if a researcher plans to study the political institution in other countries in Southeast Asia.